Dynamics of Thai Civil Society: From Democratic to Authoritarian Regime - เฉลียวบุญ ชมพูนุท (Journal of Human Rights and Peace Studies, 2016)
Under a democratic regime, the government has legal duties to provide, protect and fulfill its citizens’ rights. At the same time, civil society, based on classical liberaltheory, play important roles between the state and its citizens. On the one hand, the civil society has a role to bridge the gaps in state’s provisions,particularly in the areas where the government may not have the capacity to reach. On the other hand, some civil society groups play the role of monito- ring the state and demand the state’s support for public interest. In this role, civil society tends to confront with the government. As Thailand is currently under an authoritarian regime, the military government has put a greater control over the space and roles of the civil society. Limitation of rights and the deprivation of freedom of expression requires that civil society groups, especially those which play a monitoring role, adapt theirperspectivesand strategies in order to continue to work on public interest. This article examines the role of civil society under the democratic atmosphere and the challenges and methods used by civil society under this current repressive regime.